Phosphatidylcholine-Based Nanoemulsions for Paclitaxel and a P-Glycoprotein Inhibitor Delivery and Breast Cancer Intraductal Treatment - Giovanna Cassone Salata; Luciana B. Lopes (MDPI AG, 2022)
In this study, incorporation of the cytotoxic agent paclitaxel and the P-glycoprotein inhibitor elacridar in hyaluronic acid (HA)-modified nanoemulsions was studied for intraductal delivery and breast cancer localized treatment. To improve cytotoxicity, we investigated the incorporation of perillyl alcohol or tributyrin as components of the nanoemulsion oil phase. The nanoemulsions presented size <180 nm and negative zeta potential. Both tributyrin and perillyl alcohol increased nanoemulsion cytotoxicity in MCF-7 cells, but not in MDA-MB-231. However, perillyl alcohol reduced nanoemulsion stability in the presence of the drugs. Concomitant incorporation of paclitaxel and elacridar in HA- and tributyrin-containing nanoemulsions (PE-NETri) increased cytotoxicity and reduced IC50 by 1.6 to 3-fold in MCF-7 and MDA-MB-231 cells compared to the nanoemulsion containing only paclitaxel (P-NE). This nanoemulsion also produced a 3.3-fold reduction in the viability of MDA-MB-231 spheroids. Elacridar incorporated in the nanoemulsion was capable of inhibiting P-glycoprotein in membranes. In vivo intraductal administration of the NE containing HA resulted in a three-fold higher retention of a fluorescent marker compared to a solution or nanoemulsion without HA, demonstrating the importance of HA. The nanoemulsion produced no histological changes in the mammary tissue. These results support the potential applicability of the nanoemulsion for local breast cancer management.